Liquid crystals for luminescent concentrators: a review - Surampudi, A; Zhang, G; Singh, R; Faulkner, G; O’Brien, DC; Booth, MJ; Morris, SM (MDPI, 2023)
Luminescent optical concentrators are thin films containing fluorescent dyes that enable light collection over a wide field of view without the need to track the path of the Sun. However, a disadvantage when using luminescent concentrators is that the performance is often impeded by surface losses through these films. Liquid-crystal (LC) hosts are attractive for luminescent concentrators, as they impart, at the very least, an orientational ordering to the transition dipole moment of the dyes dispersed within these films. This enables the directivity of both the absorption and emission and can reduce surface losses by, for example, adopting the homeotropic alignment of the LC director. This article reviews the developments and applications of LCs to luminescent optical concentrators and describes the strategies that have been introduced to further combat losses by decoupling the absorption and emission processes through Förster energy transfer, the approaches employed to enhance the chemical structures of the dyes, and the methods of using alternative LC phases and external configurations. The review presents a comprehensive summary of the material combinations and the techniques that have been considered in the development of LC-based concentrator films and concludes with a discussion about the future perspectives for these exciting optical concentrators.